Catheter-Related Bloodstream Infection in Hemodialysis Patient due to Atlantibacter hermannii - Preslava M. Hristova; Alexandra S. Alexandrova; Martin Lukanov; Hristina Y. Hitkova; Biser Kirilov Borisov (Case Reports in Nephrology and Dialysis, 2023)
Atlantibacter hermannii, previously known as Escherichia hermannii, is a rare causative agent of human infections. Several reports testify that the most frequently infected patients are immunosuppressed, especially those undergoing hemodialysis. A 34-year-old man with an end-stage renal disease complained of chills, fever, and general fatigue at the end of a regular hemodialysis session. The echocardiographic examination showed vegetation located on the dialysis catheter in the right atrium. Empirical therapy was initiated with intravenous gentamicin, and after the isolation of the agent, the treatment was continued with intravenous imipenem/cilastatin. The blood cultures and the tip of the replaced catheter were positive for A. hermannii, identified by Vitek 2 Compact. Verification of the automated identification was performed using 16S sequencing. The 16S sequence product was used to query the NCBI bacterial database and revealed 99.75% identity to that of A. hermannii strain CIP 103176 16S ribosomal RNA in the NCBI GenBank database. The antimicrobial susceptibility results revealed resistance to aminopenicillins and susceptibility to all other tested antimicrobials. To our knowledge, this is the first report of catheter-related vegetation with echocardiographic confirmation and the successful eradication of A. hermannii infection in a patient undergoing hemodialysis with imipenem/cilastatin.